AB0416 Clinical and immunological association with autoantibodies to cellular antigen in a cohort of 532 sle patients from a single center. (23rd January 2014) - Fredi, M.; Cavazzana, I.; Cartella, S.; Tincani, A.; Franceschini, F.
Abstract : Background: autoantibodies (autoabs) to cellular antigens can be associated with specific clinical and immunological subsets of Systemic Lupus Erythematosus (SLE). Objectives: to analize the frequencies of different autoabs detected by counterimmunoelectrophoresis (CIE) and to describe clinical and immunological associations in a SLE cohort of patients. Methods: clinical and serological features about our cohort of SLE were collected from clinical charts. Antinuclear antibodies were detected by indirect immunofluorescence (IIF) on HEp2 cells, anti extractable nuclear antigen (ENA) by CIE using rabbit thymus and human spleen as substrate and anti-dsDNA by FARR assay. Anticardiolipin and anti-B2glycoprotein I were detected by ELISA. For statistical analysis was used Chi-squared or Fisher exact test and student t test. Multivariate analysis was performed using logistic regression model Results: we collected complete data from 532 SLE patients (pts), classified according to revised ACR criteria. Mean age at onset was 33.8 years, mean follow-up 10 years. They showed a female to male ratio of 12:1, mostly were Caucasians (96.4%). Among our pts 235 (44.1%)were positive for anti-Ro/SSA antibodies, 45 (8.4%)anti-Sm, 69(12.9%) U1RNP, 31(5.8%) anti-Ki, 8 (1.5%) anti-Ku, 4(0.7%) anti-centromere, 3(0.5%) anti-Scl70, 2(0.3%) Jo-1 and PCNA antibodies respectively. Clinical or serological features that show statistical significative association with one antibody specificity are reported in table 1 . We studied features associated with multiple antibodies with multivariate analysis, anti-U1RNP and anti-Ro/SSA resulted to be associated with malar rash (p=0.009 and 0.02respectively) and anti-U1RNP with leukopenia (p=0.0055). Patients with antibodies considered to be diagnostic markers for other connective tissue disease, such as anti-Scl70, anti-centromere and anti-Jo-1 were evaluated for overlap disease. Only 2pts anti-Scl70 positive satisfied classification criteria both for SLE and systemic sclerosis. Conclusions: in our cohort of SLE pts we observed several statistical significative associations between clinical and serological features and autoabs. These associations can be found both with common autoabs, but also with more rare one. In particular we confirmed association between anti-Ki antibodies and SLE male gender. We reported a new association between anti-Ku antibodies and African SLE pts. Disclosure of Interest: None Declared